[OP.5A.03] RELATIONSHIP BETWEEN LOCAL CAROTID STIFFNESS AND WALL-TO-LUMEN RATIO OF RETINAL ARTERIOLES. (September 2016) - Caletti, S.; Salvetti, M.; Rizzoni, D.; De Ciuceis, C.; Bertacchini, F.; Rosei, C. Agabiti; Maruelli, G.; Rubagotti, G.; Paini, A.; Colonetti, E.; Casella, E.; Rosei, E. Agabiti; et al.
Abstract : Objective: Wall-to-lumen ratio of retinal arterioles (W/L) might serve as an in-vivo parameter of microvascular damage. Few data are available on the correlation between local stiffness, evaluated at carotid artery level, and the presence of retinal abnormalities, assessed by arteriolar/venular ratio. Aim of the study was to analyse the correlation between carotid stiffness (CS) and W/L of retinal arterioles. Design and method: Methods: 227 subjects (56% female, age 55 ± 4 years, 48% hypertensives, 30% treated) underwent laboratory examinations, clinic BP measurement, carotid-femoral pulse wave velocity (aoPWV) and W/L ratio measurement. CS was determined from the relative stroke change in diameter (measured with a high-resolution echotracking system) and carotid pulse pressure (measured with applanation tonometry). Results: Results: both W/L and CS were significantly related with clinic SBP (r = 0.17, p < 0.05 and r = 0.50, p < 0.001), clinic PP (r = 0.22, p < 0.001 and r = 0.55, p < 0.001), carotid SBP (r = 0.18, p < 0.05 and r = 0.51, p < 0.001) and with carotid PP (r = 0.24, p < 0.001 and r = 0.56, p < 0.001). W/L was not significantly related with age and laboratory data while a positive correlation was observed between W/L and CS (r = 0.18, p < 0.005). At multivariate analysis CS, but not aoPWV, remained independently associated with W/L. Conclusions: Conclusions: in this quite large group of hypertensives and normotensives local carotid stiffness represents the main determinant of retinal arterioles wall to lumen ratio.